Alternatywna historia na obszarze postsowieckim: dwie trajektorie jednej idei = Alternative history in the post-Soviet space: two paths of one idea - Legeza, Siergiej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article explores the origin of alternative history as a trend of the science fiction genre in the USSR popular culture. The study considers the main development stages of this trend according to Russian and Ukrainian cultural contexts. The research allows to identify two directions of the mentioned development. The first one applies to Russian popular culture - from the analytics of the current state of the Russian statehood to the revanchism related to the "lost empire". The second one refers to Ukrainian popular culture - from the comprehension of the cultural and subjective separation of the country to the attempts of the national identity's creation. The narrative schemes of the alternative history were changing according to shifts in the Russian and Ukrainian ideological doctrines.
Keywords: kultura popularna; fantastyka; alternatywna historia; modelowanie przeszłości; popular culture; fantasy; alternative history; history modeling